2010
DOI: 10.1080/14697017.2010.516487
|View full text |Cite
|
Sign up to set email alerts
|

Organization Development: What's Actually Happening?

Abstract: A great deal of commentary and controversy about the state of organization development (OD) has to do with a lack of clarity regarding what it is about organizations that can be affected by an OD effort. Recent initiatives suggest that a new set of OD practices are emerging, based on a social constructionist orientation. With this in mind, this article aims to contribute to a theoretical understanding of what it is about organizations that can change, based on Berger and Luckmann's (1966) social constructionis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…If change is the outcome of sensemaking, and sensemaking is a social process, this positions social interaction at the heart of change (Ford & Ford, 1995;Marshak & Grant, 2008;Van Nistelrooij & Sminia, 2010). Accordingly, many contemporary approaches to change emphasize the importance of facilitated interactions between members of an organization.…”
Section: Dialoguementioning
confidence: 97%
“…If change is the outcome of sensemaking, and sensemaking is a social process, this positions social interaction at the heart of change (Ford & Ford, 1995;Marshak & Grant, 2008;Van Nistelrooij & Sminia, 2010). Accordingly, many contemporary approaches to change emphasize the importance of facilitated interactions between members of an organization.…”
Section: Dialoguementioning
confidence: 97%
“…The second and related factor is that newer forms of OD, such as dialogic OD and AI, which are based on a social constructionist perspective, have also been linked to Lewin's work (Burnes ; Oswick ; Van Nistelrooij and Sminia ). As a major review of OD by Burnes and Cooke () argues, though Lewin is often painted as a modernist with a unitary view of reality, the gestalt psychology that underpins field theory maintains that individuals and groups perceive and experience the world from their own perspectives, i.e.…”
Section: The Re‐emergence Of Field Theorymentioning
confidence: 99%
“…Wooten and White (1999) have shown that Lewin's change thinking aligns with post-modern organisation values, such as egalitarianism. Indeed, social constructionism can be seen as the ontological and epistemological foundation of Lewinian OD (Cummings & Worley, 2009;Van Nistelrooij & Sminia, 2010).…”
Section: Smith and Mackinnon: Organisation Development 119mentioning
confidence: 99%